2009
DOI: 10.2136/sssaj2008.0138
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Management for Subsurface Drip Irrigated Cotton: Ammonium Thiosulfate, Timing, and Canopy Reflectance

Abstract: In subsurface drip irrigation (SDI) systems, water constraints to cotton (Gossypium hirsutum L.) production are greatly minimized and N management becomes the main priority. Injecting N fertilizer into SDI systems should, in theory, be as efficient as the irrigation delivery system itself. The objective of this study was to test duration of N injections, addition of the nitrification inhibitor ammonium thiosulfate (ATS), and using canopy spectral reflectance to guide N injections in a 2‐yr study of SDI cotton … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…This greatly reduces the usefulness of petiole NO 3 . Yabaji et al (2009) reported that N fertilizer applications in SDI-irrigated cotton in West Texas are not effective after mid-bloom.…”
Section: Discussionmentioning
confidence: 99%
“…This greatly reduces the usefulness of petiole NO 3 . Yabaji et al (2009) reported that N fertilizer applications in SDI-irrigated cotton in West Texas are not effective after mid-bloom.…”
Section: Discussionmentioning
confidence: 99%
“…They achieved the best predictions by using reflectance ratios of the area of interest relative to a wellfertilized area. Yabaji et al 20 reported that basing in-season SSNM of drip-irrigated cotton on canopy reflectance resulted in 17-28 kg N ha-' savings in N fertilizer compared to regional N recommendations, without reducing lint and seed yields. Bronson et aJ.24 compared variable-rate N applications based on grid soil sampling to blanket regional N management in a 3-year study of center-pivot irrigated cotton.…”
Section: Introductionmentioning
confidence: 99%
“…Several field plot studies in West Texas used canopy refiectance based indices to assess in-season N status of cotton in SDI, and center-pivot fields in the SHP (Li et al, 2001;Chua et al, 2003;Bronson et al, 2003aBronson et al, , 2005Bronson et al, , 2011Yabaji et al, 2009). Reflectance-based N management was tested and resulted in less N fertilizer use than the regional soil test-yield goal based N management, without hurting yields (Chua et al, 2003;Yabaji et al, 2009;Bronson et al, 2011).…”
mentioning
confidence: 99%
“…Reflectance-based N management was tested and resulted in less N fertilizer use than the regional soil test-yield goal based N management, without hurting yields (Chua et al, 2003;Yabaji et al, 2009;Bronson et al, 2011). Previous studies in corn on the use of canopy reflectance to assess in-season N status reported that a well-fertilized reference plot or strip is mandatory to compare reflectance in the area of interest to (Varvel et al, 1997;Solari et al, 2008;Scharfand Lory, 2009;).…”
mentioning
confidence: 99%
See 1 more Smart Citation